The students’ and the Lecturers’ Perspectives towards Online Learning for Translation Course during the Pandemic Covid-19 - Gunawan Tambunsaribu; Masda Surti Simatupang (South Sulawesi Education Development (SSED), 2024)
Before the COVID-19 pandemic which broke out in early 2020, most of the classes in many universities in Indonesia were conducted offline (traditional classes). After the outbreak of COVID-19, most institutions had to do online teaching-learning due to government policies to prevent the spread of the coronavirus. Both students and educators realized that online learning was effective for them to fulfill the learning outcomes. In early 2023, many institutions in many countries started to conduct face-to-face classes again due to the decrease of the coronavirus spread. This research aims to find out the perspective of the students in the Translation class in both online and offline classes, before and after the COVID-19 pandemic. The researchers want to find out the solutions that both the students and the lecturers suggest for a better method of conducting a Translation course. This research uses a descriptive qualitative research method. The data are taken from the interview session and the questionnaires. The respondents are the students and lecturers of Translation courses at Universitas Kristen Indonesia and Universitas Gunadarma. This research found that the online teaching and learning process is effective for students and educators.